Pop-tech-flat-fab - Griffiths, Jason (Enquiry The ARCC Journal for Architectural Research, 2008)
This paper for the EAAE / ARCC 2008 addresses the theme of simultaneity between the digitaland analogue by examining the production of two projects. These are: a pair of prototype busstops built in Sioux City1 and a shade structure for downtown Phoenix in the USA. The conceptual basis for both these projects coincides with the question of how "phenomenon attached toa certain locality”2 might be created through advanced methods of digital fabrication. Both projects offer an apology for rapid prototyping techniques applied to an understanding of "contextualism”3.Both projects are presented first as a contextual and symbolic response to an interpretation of"locality” and then re-appraised in technical terms. In both projects these technical aspects aim to advance not only the methods of physical production but also the transition of design methodsto 1:1 fabrication. In the case of the Sioux City Bus Stops this idea is represented throughan analysis of two-dimensional cutting techniques and developable surfaces. In the case of thePhoenix Shade project this idea is then developed through fully associative digital models. Togetherthese projects attempt to accelerate the physical production of their symbolic and contextualcontent through a discussion on parametric modeling that allows an efficient productionof a set of different permutations. By associating the symbolic/contextual with the parametricthese projects suggest and alternative procedure to the traditional and prevalent trope of "digitalarchitecture” and its co-dependence upon explicitly biomorphic, computational and quasinaturalistic language.4